2013
DOI: 10.1115/1.4023176
|View full text |Cite
|
Sign up to set email alerts
|

Review of World Urban Heat Islands: Many Linked to Increased Mortality

Abstract: Review of World Urban Heat Islands: Many Linked to Increased MortalityMedical and health researchers have shown that fatalities during heat waves are most commonly due to respiratory and cardiovascular diseases, primarily from heat's negative effect on the cardiovascular system. In an attempt to control one's internal temperature, the body's natural instinct is to circulate large quantities of blood to the skin. However, to peiform this protective measure against overheating actually harms the body by inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 58 publications
0
45
0
1
Order By: Relevance
“…It is well known that there is a strong relationship between the increase of temperature and the emergence of heat-related illnesses, e.g., heat stress and mortalities, in cities (Patz et al, 2005;Wong et al, 2013). Although there is no any investigation addressing this issue for Ho Chi Minh City, another study on Da Nang, another major city in Vietnam, showed that hot air temperature causes heat stress and other health issues, especially in the outdoor environment (Dao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that there is a strong relationship between the increase of temperature and the emergence of heat-related illnesses, e.g., heat stress and mortalities, in cities (Patz et al, 2005;Wong et al, 2013). Although there is no any investigation addressing this issue for Ho Chi Minh City, another study on Da Nang, another major city in Vietnam, showed that hot air temperature causes heat stress and other health issues, especially in the outdoor environment (Dao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Given anticipated increases in temperature from overall global warming and urbanization, understanding the health impacts of weather under a changing climate and determinants of these associations is critical to protect public health. Previous findings have shown that urban areas are particularly vulnerable to heat-related health outcomes due to the urban heat island effect (Burkart et al, 2014; Kovats and Koppe, 2005; Tan et al, 2010; Wong et al, 2013). The urban heat island effect results in temperatures that are higher in urban areas than in surrounding rural or suburban areas and could exacerbate the effects of weather under global climate change.…”
Section: Introductionmentioning
confidence: 99%
“…That such seasonal flash floods would become more recursive and severe as global warming pro gresses, followed by severe seasonal water shortages due to lower volume flows downstream of the Himalayas, require solutions which are more permanent than mud dams. Climate change and its effects have been studied by Wong and researchers [21][22][23][24], According to Vidal [25], India plans for 292 dams on rivers ris ing in the Himalayas. Vidal stated that India, Nepal, Bhutan and Pakistan are in a "water grab" in the Himalayas, as they look for new sources of electricity to power their economies.…”
Section: Recommendationsmentioning
confidence: 99%